Effect of ginger extract on angiogenesis using CAM assay - Bashir, Muhammad Farhan; Qadir, Muhammad Imran (Bangladesh Journal of Pharmacology, 2017)
Angiogenesis performs a critical role in the embryonic growth and several pathological conditions in cancer. This study evaluated the anti-angiogenic properties of the ginger extract using CAM assay. Ginger extract was prepared by methanol. Window was made after 5 days of incubation of eggs and the ginger extract was applied on day 6 at different doses (20, 50, 75 and 150 µL). SPIP software was utilized to investigate the CAM region and diameter of blood vessels. Ginger extract proved anti-angiogenic consequence by decreasing the diameter of CAM of blood vessels. Comparable results were attained at dilution of 150 µL. The anti-angiogenic activity of ginger extract implicates its possible application for diseases where inhibition of blood vessel formation is desired. Video Clip of Methodology: 7 min 32 sec: Full screen Alternate